Analysis of the Shift Jerk of Dual Clutch Transmission - Chang Jia’nan; Sun Baoqun; Jiang Mingliang; Lu Jun (Jixie chuandong)
Taking the dual clutch transmission as analysis object,a three-state dynamics model is built.The theoretical expressions of the shifting jerk of each states during the shifting process also are deduced. Considering the circulating power and the order of the operations of two clutches,the effects of above two factors on the shift jerk during the shifting process is analyzed detailedly. A control strategy of clutches basing on the speed adjustment of engine for dual clutch transmission is proposed. After that,a simulation model is built based on Matlab/Simulink platform. The result of the simulation shows that the control strategy coming from the theory can reduce the shift jerk effectively.